2010
DOI: 10.1002/jssc.200900798
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabonomic study of lung cancer by a fully automatic hyphenated hydrophilic interaction/RPLC‐MS system

Abstract: Lung cancer is one of the most common and lethal cancers in the world. In this study, a home-devised hydrophilic interaction chromatography/RPLC-MS (HILIC/RPLC-MS) system was developed to study the urinary metabonomics of lung cancer patients. This system combined the orthogonal selectivity of HILIC and RPLC and could chromatographically reveal more comprehensive information of the urinary metabolites. Within a total analysis time of 50 min, we detected 577 polar metabolite ions on the first HILIC column and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 53 publications
4
51
2
Order By: Relevance
“…Thus, we speculated that tyrosine metabolism is also disturbed in lung cancer patients, resulting in PHPLA accumulation. The second potential biomarker we had speculated out was proline betaine (ion with t R -m/z 6.80-144.097), which also had been found in the urinary metabonomic study of lung cancer [42]. We found that the change trend of proline betaine in our plasma metabonomic study was same as the urinary metabonomic study [42].…”
Section: Effect Of the Radiotherapy On The Plasma Metabolic Pattern Isupporting
confidence: 69%
See 2 more Smart Citations
“…Thus, we speculated that tyrosine metabolism is also disturbed in lung cancer patients, resulting in PHPLA accumulation. The second potential biomarker we had speculated out was proline betaine (ion with t R -m/z 6.80-144.097), which also had been found in the urinary metabonomic study of lung cancer [42]. We found that the change trend of proline betaine in our plasma metabonomic study was same as the urinary metabonomic study [42].…”
Section: Effect Of the Radiotherapy On The Plasma Metabolic Pattern Isupporting
confidence: 69%
“…When comparing with the markers which had been found in the urinary metabonomic study [42], we found many different marker ions despite several same potential markers in the plasma. It meant that new biomarkers could be found by the plasma metabonomic study.…”
Section: Effect Of the Radiotherapy On The Plasma Metabolic Pattern Imentioning
confidence: 66%
See 1 more Smart Citation
“…Review MS-based metabolomic platforms are increasingly applied to the screening of tumor markers and have been used in recent years for colorectal cancer [39][40][41][42][43][44][45][46], lung cancer [47][48][49][50][51][52][53], papillary thyroid carcinoma [54], oral cancer [55,56] and pancreatic cancer [57]. Here, due to space limitations, the authors review the development of metabolomics in the discovery of tumor markers only for specific malignancies with high incidence, including primary liver cancer, gynecologic cancer and genitourinary cancer.…”
Section: Phenotype Classification and Early Detection Of Tumor Patientsmentioning
confidence: 99%
“…While most of the LC-MS analyses use reverse phase liquid chromatography (RP-LC) to separate metabolites before MS analysis [48], hydrophobic interaction liquid chromatography (HILIC) has emerged as another choice of separation platform for LC-MS based metabolomics [49]. HILIC is similar to normal phase LC, in that the stationary phase is polar; however, in contrast to normal phase LC, the mobile phase in HILIC uses water miscible solvents, such as acetonitrile or methanol, and also contains a substantial amount of water.…”
Section: Liquid Chromatography Mass Spectrometry (Lc-ms)mentioning
confidence: 99%